EŞARi'NiN TEOLOJiK GÖRÜŞLERi - Yar, Erkan (Fırat University, 2006)
Al-Ash'ari is one-ofthe most important Muslim theologians. His theology is the begiıming of Sunnite philosophical theology. He developed .opinions about the divine· attributes.' The .. eternal attributes of God are neither himself nor other than · himselL This is _a -paradoxical e:x"Pression' He hel d acquisition or kas b about the human · actions notifying thatGad is. the creator.of human actions and·what humans do is but to acquire tbeın; ·He is dn the npinion.·that God· has-sent prophets ·and has given them mira cl es. Eschatological matters· must ,be tak en literally -and not be explained as metaphors. To him action is not a part ofbelief. And he also put forward some political thoughts theologically.
Keywords: Religious Studies; Din Araştırmaları